DAMPAK KEHADIRAN PASAR MODERN TERHADAP PENURUNAN KECENDERUNGAN PELANGGAN PADA PASAR TRADISIONAL - Khoirunnisa, Fitria; Khoirunnisssa; Amaliyah, Putri; Catur Ramadani , Ryan; Tri Setyoko, Didik (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
Traditional markets are markets where people carry out buying and selling transactions, this can be done by bargaining. Traditional markets are usually located on the side of the road or in residential villages. Meanwhile, in modern markets such as supermarkets or mini markets, the transaction process is usually carried out by bargaining when purchasing goods. Traditional markets contain various types of shophouses and shops owned by individuals. Currently, consumer interest in modern markets is higher than traditional markets. The purpose of this article is to see consumer interest in the impact of modern markets on traditional markets. The data was collected using literature study techniques, namely articles and journals related to the titles and topics that we will discuss in this article. The results of the literature review research show the condition of traditional markets. experienced a decline in operations after this modern market emerged. People tend to prefer modern markets to buy goods, because they look at the price and the location is very comfortable